2020
DOI: 10.1029/2019jc015555
|View full text |Cite
|
Sign up to set email alerts
|

Aspect Ratio of Eddies Inferred From Argo Floats and Satellite Altimeter Data in the Ocean

Abstract: Mesoscale eddies dominate the majority of oceanic kinetic energy. The size of eddies is one of the basic properties; however, little is known about it because of lack of observations. Especially, their global vertical extent has still not been well investigated. Here, a ratio relationship of height to length scale for an eddy is derived based on dynamical constraints. Global satellite altimetry data combined with Argo float observations are used to calculate the aspect ratios of mesoscale eddies in the global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
9
1
Order By: Relevance
“…The choose of the upper 400 m is in accordance with many literature works (Vivier et al, 2002;Doney et al, 2007;Song et al, 2014), based on the consideration that the upper 400 m is thermodynamically the most energetic layer of the ocean. It has been shown that about 52% of surface-intensified eddies extend to less than 400 m in the vertical (Liu et al, 2020). An alternative limit of 700 m does not change our findings qualitatively.…”
Section: Eddy-induced Anomaliescontrasting
confidence: 63%
See 3 more Smart Citations
“…The choose of the upper 400 m is in accordance with many literature works (Vivier et al, 2002;Doney et al, 2007;Song et al, 2014), based on the consideration that the upper 400 m is thermodynamically the most energetic layer of the ocean. It has been shown that about 52% of surface-intensified eddies extend to less than 400 m in the vertical (Liu et al, 2020). An alternative limit of 700 m does not change our findings qualitatively.…”
Section: Eddy-induced Anomaliescontrasting
confidence: 63%
“…This algorithm provides eddy boundary information, which is of particular importance to this study in calculating eddy-induced anomalies. It should be noted that as in previous studies (e.g., Cheng et al, 2014;Faghmous et al, 2015;Liu et al, 2020), no strict distinction between mesoscale eddies and long baroclinic Rossby waves are made, since the two are both manifested as SSH extrema and they often coincide (Pingree and Sinha, 2001;Oliveira and Polito, 2013;Polito and Sato, 2015). Eddy trajectories are found by searching for similar eddies between the adjacent timesteps within a search radius determined by the maximum eddy propagation speed-the phase speed of long baroclinic Rossby waves.…”
Section: Eddy Identification and Trackingmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the representation of ocean mesoscale dynamics is strongly limited by the spatial coverage and temporal sampling of a given satellite mission (e.g., Bonaduce et al, 2018;Chen et al, 2021). Moreover, the temporal and spatial co-location with the available Argo profiling floats in certain areas of the ocean is affected by uneven data coverage and sampling frequency (e.g., Liu et al, 2020), which can represent a shortcoming to investigate the properties of water masses induced by the occurrence of 3D eddies.…”
Section: Introductionmentioning
confidence: 99%